A New Neighborhood Every Fall: Aging in Place in a College Town. Issue 7 (16th November 2016) - Powell, Kathleen H.
ABSTRACT: Older adults who live in residential neighborhoods adjacent to college and university campuses have a unique experience that makes them vulnerable to marginalization and displacement. As these neighborhoods become increasingly dominated by college students living in rental properties, older adults find themselves in the minority in a neighborhood where they have lived for many years. In addition, these neighborhoods are attractive to universities, city governments, and private companies for their development potential, which can result in gentrification. A year-long ethnographic study of a campus-adjacent neighborhood in a small US college town that is home to a medium-sized public university sheds light on the relationships between members of 5 stakeholder groups that have a vested interest in the neighborhood. The study highlights the need for additional research on different types of neighborhoods and their effects on aging in place in addition to outlining social work interventions in campus-adjacent neighborhoods that are designed to enhance these intergenerational spaces.